2021
DOI: 10.1111/ijac.13770
|View full text |Cite
|
Sign up to set email alerts
|

Three​‐dimensional porous poly(ε‐caprolactone)/beta‐tricalcium phosphate microsphere‐aggregated scaffold for bone tissue engineering

Abstract: In this study, porous scaffolds made of polycaprolactone (PCL)/β‐tricalcium phosphate (BTCP) biocomposite were fabricated for bone tissue engineering (BTE) applications. The microsphere‐aggregated scaffolds were prepared with various BTCP concentrations (10wt%, 20wt%, 50wt%) by the freeze‐drying method. The porosity of obtained microsphere‐aggregated scaffolds with various pore sizes was 80–85%, where this value was about 70% for the PCL/BTCP (50) sample with no microsphere formation. The results indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The porosity of these scaffolds was 80~85%. The adhesion and proliferation of bone marrow-derived MSCs seeded onto PCL/BTCP scaffolds were enhanced compared to those on PCL [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The porosity of these scaffolds was 80~85%. The adhesion and proliferation of bone marrow-derived MSCs seeded onto PCL/BTCP scaffolds were enhanced compared to those on PCL [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has also shown that adding nanoparticles to the matrix can improve cellular connections and behavior ( Gaharwar et al, 2014 ). Generally, there could be found some factors that might influence initial cell attachment, including protein absorption capability, surface free energy, roughness, and chemical characteristics of the surface ( ShiraliPour et al, 2021 ). It is clearly shown in the Figure 10 , all nanocomposite scaffolds could adequately promote cellular adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…As reported in previous studies, mineral sediments on pure PCL scaffolding are due to hydrolytic degradation of PCL, which is mainly caused by severing ester bonds on the surface of PCL fibers, which leads to the formation of a negative charge, carboxyl groups (-COOH) and hydroxyl (-OH). The basis of mineral sediments and their growth is the adsorption of calcium cations by negatively charged groups on the surface of scaffolds, which leads to the creation of hydroxyapatite crystals in the form of PO 4 ( Pitt et al, 1981 ; Kokubo, 1991 ; Persenaire et al, 2001 ; Bravo-Suárez et al, 2004 ; Leong, 2004 ; Oyane et al, 2005 ; Sugawara et al, 2005 ; Kokubo and Takadama, 2006 ; LeGeros, 2008 ; Guarino and Ambrosio, 2010 ; Yang et al, 2010 ; Cipitria et al, 2011 ; Fayyazbakhsh et al, 2012 ; Jaiswal et al, 2012 ; Krishna and Pugazhenthi, 2013 ; Gaharwar et al, 2014 ; Lakatos et al, 2014 ; Li et al, 2014 ; Wu et al, 2015 ; Halling Linder et al, 2016 ; Shafiei et al, 2016 ; Conoscenti et al, 2017 ; Kino et al, 2017 ; Mohammadi et al, 2017 ; Diaz-Rodriguez et al, 2018 ; Gandolfi et al, 2019 ; Hosseini et al, 2019 ; Iviglia et al, 2019 ; Morejón et al, 2019 ; Mozaffari et al, 2019 ; Tohidlou et al, 2019 ; Bagheri and Mahmoodzadeh, 2020 ; Baradaran et al, 2020 ; Makwana et al, 2020 ; ShiraliPour et al, 2021 ). Additionally, Many previous investigations have shown that LDH plays a significant role in osteogenesis and mineralization ( Baradaran et al, 2020 ; Cheng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By tailoring the physical and chemical properties of PCL, its degradation, biocompatibility, mechanical strength, and surface bioactivity can be modified. 4 On the other hand, blending synthetic and natural polymers enhances bioactivity and cell attachment; also, the degradation rate of the blended matrix can be modified based on its application. 5 The hydrolyzed form of collagen, gelatin, is a natural biopolymer that is widely used in medical and pharmaceutical fields due to its protein-based structure, biodegradability, biocompatibility, and commercial availability.…”
Section: Introductionmentioning
confidence: 99%